Pengaruh Capital Intencity Ratio, Free Cash Flow, Kualitas Audit, dan Leverage terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar Di BEI - Fitria Ramadhani; Sri Wahjuni Latifah; Endang Dwi Wahyuni (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
The purpose of this research is to analyze the influence of variable capital intencity ratio, free cash flow, audit quality, and leverage to earnings management action. The population in this study is manufacturing companies listed on the BEI during the period 2013-2015. Tests on the formulation using multiple regression analysis methods contained in the SPSS program. Based on the result of this research indicate that variable of capital intencity ratio, free cash flow, and audit quality do not influence to earnings management action. While the leverage variable has an influence on earnings management. This is evidenced by the average value of high sample company leverage. Management will try to manage its profits to reduce the failure rate to pay corporate liabilities.Keywords: Earnings Management, Capital Intencity Ratio, Free Cash Flow, Audit Quality, Leverage